Spirals visualizing unseen energies through an immersive installation - Espinosa, Danna Mhae Buenavista
Artmaking can be viewed as a spiritual practice and activity; a way to contemplate and visually express metaphysical beliefs that cannot always be verbally communicated or reasoned. Similarly, my personal intention is to visually present an alternative approach to looking at reality.